واقع رابطة الجيرة في الأحياء السكنية الاجتماعية الجديدة -دراسة ميدانية لحي 1026 مسكن- غليزان- (مجلة الواحات للبحوث والدراسات, 2023)
ملخص:      نعالج من خلال هذه الورقة البحثية دور الأحياء السكنية الاجتماعية، ومساهمتها في بناء ونشوء الروابط الاجتماعية، خاصة رابطة الجيرة، وذلك في ظل حركية وتطور المجتمع، وأنماط سلوك أفراده، حيث نسعى من خلال هذه الدراسة الكشف عن أهم المعايير التي يعتمد عليها الأفراد في نسج روابطهم الاجتماعية، وتقبل أنماط العيش الجماعية، مع تسليط الضوء على الاختلاف الاجتماعي والثقافي المرتبط بإقامة علاقات الجيرة بين الجيران، أو الإبقاء على التمثلات الرافضة للجار الجديد، وأنماط العيش المشترك، والتضارب بين قيم الجماعات المختلفة الوافدة في المجتمع الواحد، والكشف عن الآثار التي أفرزتها هذه الإستراتيجيات السكنية.كلمات دالة: الأحياء السكنية الاجتماعية، الروابط الاجتماعية، رابطة الجيرة، أنماط العيش.   Abstract: Abstract In this paper we examine the role of social residential neighborhoods and their contribution to the construction and establishment of social ties, particularly the neighborhood association in light of the movement and evolution of society and the behaviors of its members.Where the study seeks to reveal the most important starting points on which individuals rely to build their social ties and accept collective ways of life, highlighting the social and cultural difference on the Encourage the establishment of good neighborly relations between neighbors or maintain representations that reject the new neighbor, as well as patterns Coexistence, the conflict between the values of different groups arriving in the same society, and the detection of antiquities what resulted from this housing strategy positive and negative, although it is a social product and not economic. Keywords: social residential neighborhoods; social ties; neighborhood bonding; lifestyles.